Association between IL17 Polymorphisms and Risk of Cervical Cancer in Chinese Women. (25th September 2012) - Quan, Yi; Zhou, Bin; Wang, Yanyun; Duan, Ruiqi; Wang, Kana; Gao, Qianqian; Shi, Shaoqing; Song, Yaping; Zhang, Lin; Xi, Mingrong
Abstract : Interleukin-17 (IL-17) is a proinflammatory cytokine that is associated with inflammation, autoimmune disorders, and even tumors. Previous studies revealed that a large group of human malignant tumors have abnormally high IL-17 expression. In the present study, we analyzed two single-nucleotide polymorphisms (SNPs) in the IL17A (rs2275913) and IL17F (rs763780) in 311 cervical cancer patients and 463 controls using TaqMan assays. Our results indicated that the frequencies of AA genotype and A allele of rs2275913 were significantly different between the cervical cancer patients and controls (P = 0.008, OR = 1.32, 95% CI, 1.07–1.62). Stratified analyses revealed that the polymorphism of rs2275913 was also associated with positive peritumor intravascular cancer emboli and high clinical stage. The genotype and allele frequencies of rs763780 did not show any difference between patients and controls or relate to patient clinical characteristics. Collectively, these findings suggested that IL17 gene polymorphism rs2275913 was associated with the susceptibility as well as positive peritumor intravascular cancer emboli and high clinical stage of cervical cancer in Chinese women.